Lists of potentially inappropriate medications for older people in primary care: a systematic review of health outcomes - Rafael Cardinali Rodrigues; Gabrielle Kéfrem Alves Gomes; Bárbara Manuella Cardoso Sodré; Rodrigo Fonseca Lima; Débora Santos Lula Barros; Ana Claudia Morais Godoy Figueiredo; Cristine Miron Stefani; Dayde Lane Mendonça da Silva (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: This study is a systematic literature review of the association between lists of potentially inappropriate medications (PIM) in clinical practice and health outcomes of older adults followed up in primary health care. For this purpose, the PRISMA protocol was used to systematize the search for articles in the PubMed, Web of Science, Scopus, Cochrane Central, LIVIVO and LILACS databases, in addition to the gray literature. Studies with randomized clinical trials were selected, using explicit criteria (lists) for the identification and management of PIM in prescriptions of older patients in primary care. Of the 2,400 articles found, six were used for data extraction. The interventions resulted in significant reductions in the number of PIM and adverse drug events and, consequently, in potentially inappropriate prescriptions (PIP) in polymedicated older adults. However, there were no significant effects of the interventions on negative clinical outcomes, such as emergency room visits, hospitalizations and death, or on improving the health status of the older adults. The use of PIM lists promotes adequate medication prescriptions for older adults in primary health care, but further studies are needed to determine the impact of reducing PIM on primary clinical outcomes.